HUBUNGAN DIABETES MELITUS TIPE 2 DENGAN PENURUNAN FUNGSI KOGNITIF PADA LANSIA DI PUSKESMAS RAWA BUNTU TANGERANG SELATAN TAHUN 2021 HUBUNGAN DIABETES MELITUS TIPE 2 DENGAN PENURUNAN FUNGSI KOGNITIF PADA LANSIA DI PUSKESMAS RAWA BUNTU TANGERANG SELATAN TAHUN 2021 - Nerli Adria Sinabutar; Oryza Intan Suri; Komang Esen Ariada (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction: As humans age, it will have an impact on decreasing brain ability. The high risk of vascular dysfunction in people with type 2 diabetes mellitus is believed to be the cause of the increased risk of dementia and cognitive dysfunction. Purpose: The purpose of knowing the relationship of type 2 diabetes mellitus with decreased cognitive function in the elderly in the area of Puskesmas Rawabuntu South Tangerang 2021. Method: The design of this study was an analytic observational study with a cross-sectional approach using the Chi-Square Test. The sample of this research is 56 respondents using quota sampling technique. Result: The results of this study indicate that the number of respondents who suffer from type 2 diabetes is the same as those who do not suffer from type 2 diabetes (N, 50%). Most of the respondents experienced a decrease in severe cognitive function, especially in patients with type 2 diabetes (N, 39.4%).